What Does Voluntary Disenrollment from Medicare+Choice Plans Mean to Beneficiaries? - Harris-Kojetin, Lauren D. (CENTERS for MEDICARE & MEDICAID SERVICES, 2002)
The Balanced Budget Act (BBA) of 1997 required CMS to report publicly Medicare managed care (MMC) plan voluntary disenrollment rates. To ensure disenrollment rates would be meaningful to beneficiaries in health plan choice, CMS funded the development of surveys and reporting formats to identify and present the reasons that beneficiaries voluntarily leave plans. Public reporting of reasons on the Medicare Web site began in 2002. We discuss results from extensive audience testing of disenrollment rates and reasons materials. Medicare beneficiaries do not easily understand disenrollment. We also discuss challenges in presenting useful disenrollment information and policy implications for public reporting.